Conductor and joint test results of JT-60SA CS and EF coils using the NIFS test facility. (January 2016) - Obana, Tetsuhiro; Takahata, Kazuya; Hamaguchi, Shinji; Kizu, Kaname; Murakami, Haruyuki; Chikaraishi, Hirotaka; Noguchi, Hiroki; Kobuchi, Takashi; Moriuchi, Sadatomo; Imagawa, Shinsaku; Mito, Toshiyuki; Tsuchiya, Katsuhiko; et al.
Highlights: Test project of conductors and joints for the JT-60SA CS and EF coils was completed. Using the NIFS test facility, conductor tests and joint tests were conducted. Test results of the conductors and joints fulfilled the design requirement. Abstract: In 2007, JAEA and NIFS launched the test project to evaluate the performance of cable-in-conduit (CIC) conductors and conductor joints for the JT-60SA CS and EF coils. In this project, conductor tests for four types of coil conductor and joint tests for seven types of conductor joint have been conducted for the past eight years using the NIFS test facility. As a result, the test project indicated that the CIC conductors and conductor joints fulfill the design requirement for the CS and EF coils. In addition, the NIFS test facility is expected to be utilized as the test facility for the development of a conductor and conductor joint for the purpose of the DEMO nuclear fusion power plant, provided that the required magnetic field strength is within 9 T.